An invention of "build-then-sell" in Malaysia via the housing law - Sufian, Azlinor; Sapian, Abdul Razak (2009)
For years Malaysia has been practicing "sell-then-build" in the housing development and for years also the concept has contributed to various types of problems, mainly to house purchasers. The urge from several quarters especially the National Housebuyers Association, has be part of the cause for the government to initiate few steps in implementing the "build-then-sell" in stages. Besides several incentives in terms of policy, the first step under the law to promote the "build-then-sell" is by introducing schedule I and J in the Housing Development (Control and Licensing) Regulations 1989 (Amendment 2007). It is the aim of this paper to look into the so called "build-then-sell" according to Malaysian style which actually does not reflect the "build-then-sell" in toto. The paper then will analyze both schedule I and J above and also will consider other points that may be relevant to the issue of "build-then-sell".